2017
DOI: 10.1371/journal.pone.0170032
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Emotional and Spatial Processes: Cognitive Dysfunction in a Depressive Phenotype Produced by Long Photoperiod Exposure

Abstract: Cognitive dysfunction in depression has recently been given more attention and legitimacy as a core symptom of the disorder. However, animal investigations of depression-related cognitive deficits have generally focused on emotional or spatial memory processing. Additionally, the relationship between the cognitive and affective disturbances that are present in depression remains obscure. Interestingly, sleep disruption is one aspect of depression that can be related both to cognition and affect, and may serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…The NOR procedure was performed as previously described [41]. Briefly, the NOR procedure consisted of two habituation days, a sample phase day, and a test phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NOR procedure was performed as previously described [41]. Briefly, the NOR procedure consisted of two habituation days, a sample phase day, and a test phase.…”
Section: Methodsmentioning
confidence: 99%
“…Only the first two minutes of each video were scored, since this is the time period when animals are most sensitive to novelty and discrimination is detectable, as previously described [4143]. All videos were scored using EthoVision XT software (Noldus Information Technology, Wageningen, The Netherlands), which automatically tracks the animal’s nose-point and calculates exploration times as the amount of time the nose-point is < 2 cm from each object.…”
Section: Methodsmentioning
confidence: 99%
“…Changing dopamine and somatostatin transmission resulted in altered anxiety and depression-like behaviors. In line with this work, another study found that rats exposed to long photoperiod exhibit depressive phenotypes in the forced swimming test and cognitive deficits in the novel object recognition task [ 107 ].…”
Section: Photoperiod-induced Plasticity In Other Brain Regionssupporting
confidence: 58%
“…Rats were subjected to NOR testing following the procedure described by Barnes et al [24] at Days 27 and 28 after the daily…”
Section: Novel Object Recognition (Nor) Testmentioning
confidence: 99%